The role of architecture when integrating children with physical disabilities into full-service primary schools - Haripersadh, Nadira (My University, 2021)
Historically, persons with disabilities experienced discrimination from a social, political, and economic perspective. Globally, human rights legislation since the 1960’s has advocated inclusion. In 2001, in South Africa, Education White Paper 6 called for the transformation of ordinary public schools into full-service schools, which would provide equal access to learners with disabilities (Department of Education, 2001). A review of the number of such learners enrolled in full-service schools, in South Africa, showed a slow success rate in achieving the predetermined milestones (Department of Basic Education, 2017). This study looks into the physical accessibility of schools, that are categorised as full-service schools, in order to understand the positive and negative effects that the built environment has on the inclusion strategy. This investigation was conducted through interviews, that provided context and background to how the Full-Service School Strategy was implemented. These were augmented through universal access assessments to measure the effectiveness of the infrastructure renovations, and this was further explored through an analysis of the various factors that affect or are affected by the physical accessibility of a place. The only four full-service, public primary schools in Gauteng that had undergone universal design renovations (at the time of the study) were investigated through this research. Results showed that in all cases, the architectural changes were not compliant with universal accessibility as set out in the South African Bureau of Standards, South African National Standards 10400-Part S (2011), and provided only partial accessibility. Schools had not received adequate information on the architectural requirements for universal accessibility. A comprehensive approach, starting with awareness of technical, sociological, sensory, physical, medical, support, facilities and other requirements would be essential for the successful promotion of a more strategic and planned approach to converting mainstream schools into inclusive and barrier-free learning environments, or full-service schools
A dissertation submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Architecture by Research, 2021